Determination of Nutritional Value of Alfalfa Varieties and Lines by Using the In Vitro Method and Gas Production Technique - BOGA, Mustafa; Ayasan, Tugay (Journal of the Hellenic Veterinary Medical Society, 2022)
This study was organized to determine the nutritional value of different alfalfa varieties and lines selected within the scope of the “Cukurova Region Alfalfa Breeding Project”, conducted at the Eastern Mediterranean Agricultural Research Institute, by using the in vitro gas production technique. In the project, Nimet was certified as a new variety. The used alfalfa lines were YSH 26-12, YSH 23-9, YSH 21-1, YSH 27-9, YSH 37-12, YSH 35-11, YSH 28-6, YSH 16-11, YSH 14-3, and YSH 11-4. The certified Nimet variety was used as a control. Alfalfas have been harvested in April, at the beginning of blooming. Chemical composition, metabolic energy (ME), net energy lactation (NEL), and organic matter digestibility (OMD) of the certified Nimet variety with 10 different alfalfa lines used in the experiment were determined by Hohenheim in vitro gas production technique. The incubation times in the Hohenheim gas production technique are 3, 6, 9, 12, 24, 48, 72 and 96th hours. Crude protein (CP), crude cellulose (CC), NDF, and ADF contents of the alfalfa varieties and lines ranged between 19.06-22.40%, 24.90-33.30%, 33.16-45.73%, and 30.77-39.75%, respectively. After 96-hour incubation, the highest total gas production (GP) was found at the YSH 11-4 line (45.32 ml) (P < 0.05). While ME, OMD and NEL contents were found to be high at the YSH 11-4 line, ME and OMD values were statistically different from the YSH 28-6, YSH 16-11, YSH 14-3, and YSH 21-1 lines. On the other hand, NEL values were determined different from YSH 23-9, YSH 21-1, YSH 28-6, YSH 16-11, YSH 14-3 lines.